(untitled) (Research, Society and Development, 2021)
The Emergency Contraception, also known as “morning-after pill” is a birth control method widely used by teenagers, however its mention is insufficient or non-existent in the school. Therefore, this study aimed to investigate the emergency contraception pill approach inside classes of Biology teachers working at public and private schools in Campos dos Goytacazes/RJ with regard to the emergency contraception and its efects, the presence inside textbooks, the theme relevance and the difficulty in approaching in classes. It was also investigated the use of active learning methodologies by the teachers. Qualitative research data were collected throughout the online questionnaire. The study’s results reveal the underdeveloped approach of the topic “emergency contraception pill” in the schools by both teachers and teaching materials and the difficulties encountered by teachers in relation, mainly, to the myths of the effects of AE and to taboos on the subject. Futhermore, many teachers mistakenly considered EC to be abortive. Therefore, it is necessary to deepen this theme in didactic materials and among teachers to increase the knowledge of students and society and, thus, reduce prejudices and myths about emergency contraception.